PODRĘCZNIK DO JĘZYKA NIEMIECKIEGO W OCENIE NAUCZYCIELA I UCZNIA - Jarząbek, Alina Dorota (Neofilolog, 2018)
The following article presents the results of a survey in which teachers and students were asked to give their opinion on the German textbook Weltour or Meine Welttour. So far no alternative has been found for a textbook as a central medium of the lesson. This means, however, that both teachers and students assess its form and contents and see its strengths and weaknesses. The results of this unrepresentative study may be of interest to teachers, but above all to authors of language textbooks and publications. It is they who eventually decide on the final shape of such books, whose contents have not only to respect the requirements of the core curriculum, but also respond to students’ communication and intellectual needs.